A subtribo Ecliptinae Less. (Heliantheae: Asteraceae) no Pantanal brasileiro - Mendes, Daniel de Menezes (2024)
This study aims to present a floristic inventory and taxonomic treatment of the subtribe Ecliptinae Less., one of the most important subtribes within Heliantheae Cass. (Asteraceae), for the Brazilian Pantanal. The Pantanal is in south-central South America and most of its territorial extension is on Brazilian soil (140,000 km2), where it occupies the states of Mato Grosso (MT) and Mato Grosso do Sul (MS). The Asteraceae family is one of the most diverse in Brazil but still lacks floristic inventories and taxonomic treatments in key areas of the country, such as the Pantanal. Aiming to integrate data from herbaria, online databases, and field expeditions, this work resulted in morphological descriptions, identification keys, taxonomic comments, and species phenological, conservation, and distribution data. Thus, 27 species are reported for this study area, divided into 13 genera, four endemic species, restricted to the Pantanal. In addition, 10 new occurrences for the family are documented here: seven for the Pantanal, two for the state of Mato Grosso do Sul, and 1 for Brazil, as well as the discovery of a new species for science. However, there was a gap in the conservation status of the species, 18 of which were not assessed. This dissertation is divided into two chapters. The first chapter contains the taxonomic treatment of the subtribe Ecliptinae Less. (Heliantheae: Asteraceae) for the Brazilian Pantanal, and the second chapter describes a new species endemic to the Pantanal.